Modulation of a rapid neurotransmitter receptor-ion channel by membrane lipids - Barrantes, Francisco José (2024)
Fil: Barrantes, Francisco José. Pontificia Universidad Católica Argentina. Instituto de Investigaciones Biomédicas; Argentina